Peritoneal B cells regulate the numbers of allotype-matched pre-B and B cells in bone marrow. - Marcos, M A (1991)
The mechanisms regulating growth and differentiation of B-cell precursors in adult bone marrow (BM) and/or selecting immunocompetent cells for peripheral export are poorly understood. We report here that small numbers of activated peritoneal B cells selectively suppress the numbers of small pre-B (B220+IgM-) and B (B220+IgM+) cells in BM, if transferred into syngeneic adult mice. No significant alterations are detected in other BM cell lineages or in peripheral lymphocytes of recipient mice. Both CD5+ and CD5- peritoneal B cells display this activity, but the same or higher numbers of similarly activated splenic B cells have no effect. Suppression of B-lineage cells is independent of T lymphocytes but requires that both donor and recipient are matched for immunoglobulin allotypes. These findings provide evidence for regulation of BM B-cell production by peripheral B cells, especially when located in the peritoneal cavity, and ascribe regulatory roles to the peritoneal B-cell compartment. They also could contribute to understanding the control of total B-lymphocyte numbers in the organism.